Persons in Nature: Toward an Applicable and Unified Environmental Ethics - Ferré, Frederick (Zygon, 1993)
Abstract. Two major contenders for the role of robust environmental ethics claim our allegiance. One is Baird Callicott's, based on the land ethic formulated by Aldo Leopold; the other is that of Holmes Rolston, 111, sharply distinguishing environmental from social (human) ethics. Despite their many strengths, neither gives us the vision we need. Callicott's ethic leaves too much out of his picture; Rolston's leaves too much disconnected between nature and humankind. A really usable environmental ethic needs to be both comprehensive and integrated. For that, we need a worldview that includes the human in nature but also affirms the unique values of personhood.